-5-2x+x=3

Simple and best practice solution for -5-2x+x=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5-2x+x=3 equation:


Simplifying
-5 + -2x + x = 3

Combine like terms: -2x + x = -1x
-5 + -1x = 3

Solving
-5 + -1x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -1x = 3 + 5

Combine like terms: -5 + 5 = 0
0 + -1x = 3 + 5
-1x = 3 + 5

Combine like terms: 3 + 5 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| -2500-4.05=3000 | | -5(x+12)-13-=-24 | | 4.3b+5=8.1 | | 8.5x^3=79.687x+165.9891 | | 2x^2+7x-2=-2x^2+2x | | x^2+m+7=0 | | 7(x+2)+2=8 | | 5/7n-1=11 | | f(x)=x^5-3x^3+12x | | 3x+3-x=19 | | y+5=12*10 | | (9x+5)=(6x+5) | | 0.2a/4-10=2 | | -3(x-4)-15=-12 | | 2x-3=-7x+105 | | 50+3x^2=2 | | 30/20x=11/20 | | Y-6/y-2 | | f(t)=-16t^2+96t+3 | | a/6+2=4 | | 10x+20y+8=0 | | 26x-26=15 | | -7(7b+4)=119 | | 10x-4=5x+20 | | -3z-2/2=5 | | 6x(x-1)=4x+4 | | 2a/3.1-4=6 | | 3x+14=-16x-2x | | -3(2-8n)=186 | | 4x+3(5-13)=132 | | 2x+3y-8z=89 | | 6x+2(x+7)=-10 |

Equations solver categories